2016
DOI: 10.1088/2040-8986/19/1/013003
|View full text |Cite
|
Sign up to set email alerts
|

Photobiomodulation and the brain: a new paradigm

Abstract: Transcranial photobiomodulation (PBM) also known as low level laser therapy (tLLLT) relies on the use of red/NIR light to stimulate, preserve and regenerate cells and tissues. The mechanism of action involves photon absorption in the mitochondria (cytochrome c oxidase), and ion channels in cells leading to activation of signaling pathways, up-regulation of transcription factors, and increased expression of protective genes. We have studied PBM for treating traumatic brain injury (TBI) in mice using a NIR laser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
136
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(141 citation statements)
references
References 103 publications
(143 reference statements)
2
136
0
3
Order By: Relevance
“…This data supports the suggestion that at certain point, the cytoplasmic LDs, instead of playing a protective role, become toxic for cells and trigger cell death . We thus suggest that PBM may cause lipid peroxidation and/or alterations in the lipid content through modulation of mitochondrial ROS production , resulting in triggering excessive LDs formation and subsequent cell death . In order to verify this hypothesis, we monitored the level of ROS generation in HeLa cells before and after irradiation with 0.3 J/cm 2 (Figure ).…”
Section: Resultssupporting
confidence: 78%
“…This data supports the suggestion that at certain point, the cytoplasmic LDs, instead of playing a protective role, become toxic for cells and trigger cell death . We thus suggest that PBM may cause lipid peroxidation and/or alterations in the lipid content through modulation of mitochondrial ROS production , resulting in triggering excessive LDs formation and subsequent cell death . In order to verify this hypothesis, we monitored the level of ROS generation in HeLa cells before and after irradiation with 0.3 J/cm 2 (Figure ).…”
Section: Resultssupporting
confidence: 78%
“…The best‐known medical applications of PBM have been for indications, including stimulation of wound healing (Hopkins, McLoda, Seegmiller, Baxter, ; Kovacs, Mester, & Gorog, ), reduction of pain, reduction of inflammation in orthopedic and musculoskeletal conditions (Aimbire et al, ; Gam, Thorsen, & Lonnberg, ), and mitigation of cancer therapy side effects (Zecha et al, ; Zecha et al, ). However, in recent years, there has been growing interest in the use of PBM in various brain disorders (Hamblin, ; Hennessy & Hamblin, ; Naeser & Hamblin, ; Naeser & Hamblin, ). The (almost) complete lack of any adverse side effects of PBM, coupled with the growing disillusion with pharmaceutical drugs that affect brain function, have combined together to suggest an alternative physical therapy approach to improving brain function.…”
Section: Introductionmentioning
confidence: 99%
“…This process involves a respiratory chain of five enzyme complexes which, if altered, would influence ATP synthesis. It has been suggested that tPBM, by delivering photons (energy particles) to the tissue, may promote one of such complexes -cytochrome c oxidase (CCO) or respiratory chain complex IV -restoring or enhancing ATP production and leading to more energy available for neuronal activity (Hennessy & Hamblin, 2017). Several studies reported an upregulation effect on CCO from both the LED and laser light therapy at or close to 830 nm, which led to the neuronal increase in energy production (Mochizuki-Oda et al, 2002;Wong-Riley et al, 2005).…”
Section: Introductionmentioning
confidence: 99%